The practice and theory of property in seventeenth-century Bengal. (April 2017) - Wright, Samuel
This study reconstructs the connected history of socio-economic and intellectual practices related to property in seventeenth-century Bengal. From the perspective of socio-economic practices, this study is concerned with the legal transfer of immovable property between individuals. From the perspective of intellectual practice, this study is concerned with how property was understood as an analytical category that stood in a particular relation to an individual. Their connected history is examined by analysing socio-economic practices exemplified in a number of documents detailing the sale and donation of land and then situating these practices within the scholarly analysis of property undertaken by authors within the discipline of nyāya—the Sanskrit discipline dealing primarily with ontology and epistemology. In the first section of the essay, I undertake a detailed examination of available land documents in order to highlight particular conceptions of property. In the second section of the essay, I draw out theoretical issues examined in nyāya texts that relate directly to the concepts expressed in the land documents. In the third and final section of the essay, I discuss the shared language and shared concepts between the documents and nyāya texts. This last section also addresses how the nyāya analysis of property facilitates a better understanding of claims in the documents and what nyāya authors may have been doing in writing about property.